POLISH-NEW ZEALAND ECONOMIC TIES: LEGAL PERSPECTIVE ON THE CURRENT STATE OF TRADE - Siekiera, Joanna (Juvenis scientia, 2019)
The purpose of this article is an attempt to explain the contemporary Polish-New Zealand economic relations, as well as potential development of the further cooperation. The relatively new diplomatic relations between Warsaw and Wellington are not enough studied and therefore they require more research. Legal framework is an obvious factor, which can be seen both in the methods of soft and hard law. Understanding history and characteristic marks of this relation would allow developing economic cooperation but also establishing it in the branches of national economy where such collaboration does not exist yet. Both countries perceive one another as an important, trust-based representative of appropriately the Central-East Europe and the South Pacific. Cooperating with each other, Poland and New Zealand might not only increase their bilateral trade exchange, but also become a key economic associate within the partner region.